2019
DOI: 10.1007/s00464-019-07192-0
|View full text |Cite
|
Sign up to set email alerts
|

Population-based analysis on predictors for lymph node metastasis in T1 colon cancer

Abstract: Background In this study, we aimed to identify independent predictive factors for lymph node metastasis (LNM) in T1 colon cancer. Methods Data of 8056 eligible patients were retrospectively collected from the Surveillance, Epidemiology, and End Results (SEER) database during 2004-2012. We performed logistic regression analysis to identify predictive factors for LNM. Both unadjusted and adjusted Cox regression analyses were used to determine the association between LNM and patient survival. Finally, we used com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
(44 reference statements)
2
16
1
Order By: Relevance
“…Furthermore, only tumor size ≥ 3 cm showed an elevated risk of regional LNM (OR = 1.316, 95%CI: 1.016-1.706, P = 0.038). Like other studies concerning colorectal cancer [21][22][23], Consistent with our discovered that tumor size was a predictive factor for the risk of LNM in T1 colorectal cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, only tumor size ≥ 3 cm showed an elevated risk of regional LNM (OR = 1.316, 95%CI: 1.016-1.706, P = 0.038). Like other studies concerning colorectal cancer [21][22][23], Consistent with our discovered that tumor size was a predictive factor for the risk of LNM in T1 colorectal cancer.…”
Section: Discussionsupporting
confidence: 92%
“…T1 colon cancer, which refers to carcinoma with invasion confined to the submucosa, however, had an approximately 10% probability of experiencing lymph node metastases and therefore requires radical intestinal resection with lymph node dissection. Many studies have previously evaluated the risk factors for lymph node metastasis in T1 colon cancer, however, differences in opinion have always existed (3,5,(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the diagnosis of young CRC patients has increased. Relevant research has demonstrated that age was an independent predictive factor of LNM in T1‐2 CRC patients, with younger age associated with more promising outcomes 17,18 . Xu et al 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Relevant research has demonstrated that age was an independent predictive factor of LNM in T1‐2 CRC patients, with younger age associated with more promising outcomes 17,18 . Xu et al 18 . argued that the risk of LNM in patients aged 65–79 and over 80 years decreased to approximately 0.65 and 0.44, respectively, compared with patients under 49 years old.…”
Section: Discussionmentioning
confidence: 99%